2019
DOI: 10.3390/c5030055
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Behavior and Microscopic Factors of Electron Emission from Chained Nanocarbon Coatings

Abstract: The carbyne-containing films based on linear-chain carbon are promising materials for the manufacture of electronic equipment components. These carbyne-containing materials can be used as active elements of computational electronics and as ultra-miniature sensors of gaseous environment. The temperature studies of the electrical characteristics of carbyne-containing films by most of the scientific groups are limited to the low temperature range in which the quantum properties of nanostructures are most pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The structure of the bonds in the grown carbon-based nanomatrices can be programmed by the processes of self-organization and autosynchronization of the growing nanostructures. A number of experimental studies show that the sp-bonds and the sp-hybridized carbon nanostructures are formed only in a narrow range of optimal ion-stimulated pulse-plasma deposition parameters and modes [ 33 ].…”
Section: Features and Synthesis Of The Functionalizing Nanocarriersmentioning
confidence: 99%
“…The structure of the bonds in the grown carbon-based nanomatrices can be programmed by the processes of self-organization and autosynchronization of the growing nanostructures. A number of experimental studies show that the sp-bonds and the sp-hybridized carbon nanostructures are formed only in a narrow range of optimal ion-stimulated pulse-plasma deposition parameters and modes [ 33 ].…”
Section: Features and Synthesis Of The Functionalizing Nanocarriersmentioning
confidence: 99%
“…Frontier 1D linear carbon chains produced by carbon plasma ion-stimulated condensation were studied both theoretically, by density functional theory, and experimentally in a temperature range up to 400 • C [8]. The reported results showed that a combination of substrate structure and terminal group type of the carbon chain influences the work function of the material, a property exploitable both for the electronic and sensing applications of these systems.…”
mentioning
confidence: 99%